Ethnopharmacological Knowledge and Antioxidant Propensities of Argania spinosa L. from Morocco - Mohamed El Yamani; Rachid Ijjouk; Kholoud Kahime; Yahia Rharrabti (Hindawi Limited, 2024)
This work aims to merge ethnopharmacological knowledge with biochemical analysis to enrich our understanding of the significance of the argan tree (Argania spinosa (L.) Skeels) and to valorize its crucial role in the province of Essaouira (Morocco). First, a survey was conducted using semistructured interviews with 325 informants from Essaouira province between February and April 2023. The interviews covered sociodemographic data and information on argan tree uses, whether for therapeutic, cosmetic, or food purposes (i.e., applications, parts used, preparation, and administration). Second, phenolic extracts were prepared from various parts of the argan tree (i.e., leaves, kernels, nut shells, press cake, and oil) and then assessed for their antioxidant potential to scientifically validate their traditional uses. The evaluation of antioxidant activity focused on their free radical scavenging and reducing capacities, using DPPH and FRAP assays. Findings confirmed the cultural significance of the argan tree for the local population, as well as their strong dependence on its products. Indeed, it was noted that argan-based products are widely favored in traditional cuisine, with a prevalence of 83.4%; Amlou is the most commonly consumed food. Therapeutic and cosmetic applications accounted for 48.6% and 28.0%, respectively, predominantly for treating skin and subcutaneous issues (69.5%) and diabetes (19.7%). Argan oil was the most cited argan product used, often consumed raw (97.5%), followed by almonds (22.8%). Cataplasm (26.1%) and maceration (24.6%) were preferred for argan derivative preparation. External application (50.1%) was the primary administration method, followed by oral consumption (38.1%) and massage (27.7%). For in vitro assays, the argan tree could prove to be a promising source of phenolic compounds, especially in the leaves (>4 times richer than other parts, 231.046 ± 5.090 mg GAE/g DW). DPPH and FRAP tests demonstrated notable antiradical potential and reducing power, concentration-dependent. Leaf-derived phenolic extracts exhibited the highest free radical scavenging potential (IC50 = 0.589 ± 0.005 mg/ml) and the best reducing capacity (IC50 = 0.420 ± 0.005 mg/ml), although these potencies remained below the standard used. This study represents valuable documentation that can serve to preserve information on the use of argan products while exploring their phytochemical and pharmacological properties.